Feminist activism and the politics of reform: When and why do states respond to demands for gender-equality policies? - Anne Marie Goetz; Rob Jenkins (United Nations Research Institute for Social Development (UNRISD), 2016)
Under what conditions is gender-equality policy advocacy successful? This paper examines a segment of the growing quantitative comparative political science literature that seeks to answer this question. Recent scholarship emphasizes such factors as the strength of women's movements and the forms of opposition to which their policy demands gives rise. Variables such as the nature of the state or the economy, are also seen strongly to influence whether women mobilize to make claims on the state, the issues they politicize and their chances of success. However, one consequence of focusing on institutional factors is that the role of strategic choices made by feminist policy advocates is underestimated in explaining their successes. The article argues that understanding variation in the outcomes achieved by women's rights advocates requires close attention to the strategic capacity of policy entrepreneurs, assessed in terms of three inter-related political skills: (i) "framing" policy demands; (ii) forming and managing civic alliances; and (iii) engaging with state entities without compromising organizational autonomy.
Additional information: Prepared for the UNRISD project on: When and Why Do States Respond to Women's Claims? Understanding Gender-Egalitarian Policy Change in Asia
Keywords: 330; feminism; policy reform; civil society; social movements